Upaya Meningkatkan Kemampuan Pemecahan Masalah Matematika Menggunakan Metode Problem Solving (PTK Pembelajaran Matematika Kelas VII Semester Genap SMP Negeri 1 Teras Tahun Ajaran 2015/2016) - Saifuddin, fata, Drs. Ariyanto, M.Pd (2016)
This study aims to describe the improvement on seventh grade students of junior high school 1 Teras in solving math problem by using problem metode. This study belongs to classroom action research. The technique used for collecting data were observation, test, field notes, and documentation. The technique used for analysis data were data reduction, data presentation and data verification. For the validity of the data, it was used the triangulation investigator. The results showed that the improvement of junior high school 1 Teras student in solving math problem ability can be seen from 1) understanding the problem, from 10 students (31,25%) to 30 students (93,75%), 2) planning to solve the problem, from 7 students (21.875%) to 23 students (71,875%), 3) implementing the planning to solve problems, from 9 students (28,125%) to 21 students (65,625%) and 4) look back on the results obtained, from 6 students (18,75%) to 22 students (68,75%). Based on the analysis, it can be concluded that the applying of problem solving metode can improve math problem solving ability.